Soft sponges with tricky tree: On the phylogeny of dictyoceratid sponges. (28th January 2020) - Erpenbeck, Dirk; Galitz, Adrian; Ekins, Merrick; Cook, Steve de C.; van Soest, Rob W. M.; Hooper, John N. A.; Wörheide, Gert
Abstract: Keratose (horny) sponges constitute a very difficult group of Porifera in terms of taxonomy due to their paucity of diagnostic morphological features. (Most) keratose sponges possess no mineral skeletal elements, but an arrangement of organic (spongin) fibers, with little taxonomic or phylogenetic information. Molecular phylogenetics have targeted this evolutionary and biochemically important lineage numerous times, but the conservative nature of popular markers combined with ambiguous identification of the sponge material has so far prevented any robust phylogeny. In the following study, we provide a phylogenetic hypothesis of the keratose order Dictyoceratida based on nuclear markers of higher resolution potential ( ITS and 28S C‐region), and particularly aim for the inclusion of type specimens as reference material. Our results are compared with previously published data of CO1, 18S, and 28S (D3‐D5) data, and indicate the paraphyly of the largest dictyoceratid family, the Thorectidae, due to a sister group relationship of its subfamily Phyllospongiinae with Family Spongiidae. Irciniidae can be recovered as monophyletic. Results on genus level and implications on phylogenetic signals of the most frequently described morphological characters are discussed. Abstract : Dictyoceratid sponge phylogeny was reconstructed with ITS and 28S (C‐region) rRNA data and compared with CO1, 18S, and 28S (D3‐D5) data. Type material was included, where possible. Thorectidae and its subfamily Thorectinae are paraphyletic. Phyllospongiinae are sister to Spongiidae. Phylogenetic signal of taxonomic relevant morphological characters is low.